The Resuscitation Room of the Future: A Systematic Review of Smart Technology and Integrated Monitoring in Critical Care Resuscitation - Alenezi, Thamer Abdullah; Ahmed Abdulaziz Alanazi; Hamoud Zaki Alanazi; Mansuor Farhan Alenzi; Yahia Nafaa Alenez; Musallam Humidan ALanzi; Abdullah Owaid Alanazi; Abdulrahman Mohammed Alanazi; Bandar Dali Zaidan Al-Hazmi; Abdulaziz Khalaf Habib Alanazi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The resuscitation room is a high-stakes, time-sensitive environment where clinical decisions need to be swift and accurate. Traditional, disconnected monitoring systems and manual interventions result in cognitive overload and delay recognition and suboptimal care. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To synthesize the current evidence and conceptual frameworks for the "resuscitation room of the future," focusing on the role of noninvasive hemodynamic monitoring, continuous capnography, automated CPR devices, and smart intravenous pumps with electronic medical record integration. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Literature searches were performed in PubMed, Scopus, Web of Science, IEEE Xplore, and CINAHL for peer-reviewed articles, conference proceedings, and white papers from 2013 through 2025. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The integration of these technologies demonstrates significant benefits. The non-invasive hemodynamic monitors can provide continuous, real-time data on cardiac output and fluid responsiveness to guide more precise resuscitation. Universal continuous capnography enhances the safety of procedural sedation and confirms endotracheal tube placement while serving as a prognostic marker in cardiac arrest. The automated CPR devices provide consistent, high-quality chest compressions and facilitate procedures during transport. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The resuscitation room is a rapidly evolving environment that will be highly integrated and dependent on data. Smart technologies and integrated monitoring systems hold great promise for decreasing human error, optimizing workflow, and enhancing the precision of resuscitative care. Future utilization will have to overcome the challenges of cost, interoperability, data security, and requirements for robust training if the full potential of this technological transformation is to be completely realized.